Search for lepton-flavour-violating decays of the Higgs and Z bosons with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (The European physical journal. C, Particles and fields, 2017)
Direct searches for lepton flavour violation in decays of the Higgs and Z bosons with the ATLAS detector at the LHC are presented. The following three decays are considered: H→eτH→eτH→ eτ , H→μτH→μτH→ μ τ , and Z→μτZ→μτZ→ μ τ . The searches are based on the data sample of proton-proton collisions collected by the ATLAS detector corresponding to an integrated luminosity of 20.3 fb−1fb−1fb^{-1} at a centre-of-mass energy of s√=8s=8\sqrt{s}=8 TeV. No significant excess is observed, and upper limits on the lepton-flavour-violating branching ratios are set at the 95%%% confidence level: Br(H→eτ)<1.04%(H→eτ)<1.04%(H→ eτ )<1.04%, Br(H→μτ)<1.43%(H→μτ)<1.43%(H→ μ τ )<1.43%, and Br(Z→μτ)<1.69×10−5(Z→μτ)<1.69×10−5(Z→ μ τ )<1.69× 10^{-5}.